What is known about consumer nutrition environments in Australia? A scoping review of the literature. - Pulker, Claire; Thornton, L.; Trapp, G. (2018)
Objective: Food environments can influence food selection and hold the potential to reduce obesity, non-communicable diseases and their inequalities. 'Consumer nutrition environments' describe what consumers encounter within a food retail outlet, including products, price, promotion and placement. This study aimed to summarize the attributes that have been examined in existing peer-reviewed studies of Australian consumer nutrition environments, identify knowledge gaps and provide recommendations for future research. Methods: A systematic search of peer-reviewed literature was conducted. Sixty-six studies that assessed an aspect of within-store consumer nutrition environments were included. Results: Most studies were published from 2011 onwards and were conducted in capital cities and in supermarkets. Studies assessed the domains of product (40/66), price (26/66), promotion (16/66) and placement (6/66). The most common research themes identified were assessment of the impact of area socioeconomic status (13/66), remoteness (9/66) and food outlet type (7/66) on healthy food prices; change in price of healthy foods (6/66); variety of healthy foods (5/66); and prevalence of unhealthy child-orientated products (5/66). Conclusions: This scoping review identified a large number of knowledge gaps. Recommended priorities for researchers are as follows: (1) develop consistent observational methodology, (2) consider consumer nutrition environments in rural and remote communities, (3) develop an understanding of food service outlets, (4) build on existing evidence in all four domains of product, price, placement and promotion and (5) determine effective policy and store-based interventions to increase healthy food selection.